PENGARUH LOKASI PERSEPSI HARGA DAN KERAGAMAN PRODUK TERHADAP MINAT BELI PADA PASAR TRADISIONAL KERENENG KOTA DENPASAR - Ni Made Mini Artini; Oktavianus Sumardana Pratama; Kadek Intan Rusmayanthi (Universitas PGRI Yogyakarta, 2026)
Purchase interest reflects consumer engagement and the likelihood of acquisition. Despite the enduring popularity of traditional markets, the Kereneng Traditional Market in Denpasar faces declining consumer interest due to challenges in market organization, price-quality discrepancies, and limited product assortments. This study aims to analyze the impact of location, price perception, and product diversity on purchase interest at the Kereneng Traditional Market. Using a quantitative methodology, the research sampled 100 consumers who had visited the market more than twice. Data were analyzed using validity and reliability tests, classical assumption evaluations, multiple linear regression, F-tests, and t-tests. The findings reveal that location, price perception, and product variety exert significant effects on purchase interest, both simultaneously and partially. These results suggest that optimizing market layout, maintaining price-quality alignment, and diversifying product offerings are critical strategies for revitalizing consumer engagement at the Kereneng Traditional Market.